A modified model to predict the ballistic limit of a cubic fragment penetrating Kevlar / titanium fiber metal laminate. (October 2022) - Zhu, Zhiyuan; Li, Xiaobin; Yang, Rui; Ye, Zhenzhou; Teng, Qinghu
Highlights: A series of high-velocity impact tests on Kevlar/titanium FML are conducted. A series of formulas are proposed to predict the width and height of mushroom deformation of a cubic fragment more accurately. Energy dissipation of fragment deformation has been considered in the modified model to predict the ballistic limit in a more accurate way. Based on the modified model, a semi-theoretical formula is proposed to more simply predict the ballistic limit. Abstract: Fiber-Metal laminate (FML) is widely used in marine, military, and aerospace fields for structural protection due to its lightweight and high strength. Compared with the expensive impact experiments, a simple analytical method to predict the ballistic limit of FML is more effective and efficient. In the study, a total of 8 groups of experimental tests have been designed and implemented to investigate the ballistic resistance of bi-metal 2/1 FML which consists of two Ti-6Al-4V skins and a Kevlar core made of Kevlar-129/E54-epoxy resin. A general ballistic impact system is used to provide impact velocity greater than 800 m/s in the tests. All the specimens include the front and rear titanium skin in the same thickness, and the Kevlar core in the middle. In addition, a modified theory based on the energy dissipation is proposed to consider the effects of fragment deformation, which has been neglected by other researchers. Several modified theoretical formulas are initiated and then validated by the experimental data. As a result, the residual ballistic velocities of FMLs can be calculated from the modified theoretical formulas. It is found that the modified model can predict the ballistic limit of FML and analyze energy absorption, with certain application prospects.